IITA's Ifedayo celebrates International Youth Day 2022 | #iyd2022 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Commemorating the #iyd2022, Ibironke recounts how his work here at the International Institute of Tropical Agriculture has given him a voice in Nigeria's agricultural space.